Salvage Surgery in Recurrent Oral Squamous Cell Carcinoma - Shetty, K. S. Rathan; Kurle, Vinayak; Greeshma, P.; Ganga, Veena B.; Murthy, Samskruthi P.; Thammaiah, Siddappa K.; Prasad, P. Krishna; Chavan, Purushottham; Halkud, Rajshekar; Krishnappa, R. (Frontiers in Oral Health, 2022)
More than half of oral cancer patients recur even after multimodality treatment and recurrent oral cancers carry poorer prognosis when compared to other sites of head and neck. The best survival outcome in recurrent setting can be achieved by salvage surgery however objective criteria to select ideal candidate for salvage surgery is difficult to frame as the outcome depends on various treatment , tumour and patient related factors. The following review is aimed at summarising various tumour and treatment related factors that guide our decision making to optimize oncologic and functional outcome in surgical salvage setting for recurrent oral cancers. Short disease free interval, advanced recurrent and primary tumour stage, extra capsular spread and positive tumour margins in recurrent tumour , regional and locoregional recurrence and multimodality treatment of primary tumour all portend worser outcome after surgical salvage. Quality of life after surgical intervention has shown improvement over one year with drastic drop in pain scores . various trials are underway evaluating combination of immunotherapy and surgical salvage in recurrent head and neck tumours including oral cavity which may widen our indications for salvage surgery with improved survival and preserved organ function.